Altered GABAergic Homeostasis in the Striatum of Dopamine Transporter Knockout Rats - Targa, Giorgia; Rizzi, Beatrice; Mottarlini, Francesca; Gainetdinov, Raul R.; Leo, Damiana; Fumagalli, Fabio; Caffino, Lucia (Current Neuropharmacology, 2025)
BackgroundIt is now widely established that dopamine, despite its nature as a slow-acting biogenic monoamine, modulates fast neurotransmitters such as GABA. However, the mechanism through which this occurs still needs to be fully elucidated. The dopamine transporter (DAT) is the primary regulator of dopamine homeostasis, controlling extracellular levels of dopamine as well as its storage in vesicles.MethodsHere, we took advantage of the availability of dopamine transporter knockout (DAT-/-) rats, which provide a unique opportunity to investigate the response of the GABAergic system under hyperactivity of the dopaminergic system, a condition found in different disorders of the Central Nervous System. The expression levels of GABAergic markers have been evaluated by means of western blot in the whole homogenate, cytosolic fraction, and post-synaptic density of the striatum of male DAT-/- rats.ResultsWe found a widespread down-regulation of GABAergic markers in the striatum of DAT-/- rats. Our data show that DA overactivity critically reorganizes the striatal GABAergic synapse in a way that GABA neurotransmission appears to be toned down. Such changes are equally distributed among proteins regulating GABA synthesis (GAD67), release (vGAT) and reuptake (GAT1, GAT3). It also involves the main subunits of GABA receptors (GABA-A α1, α2, β1; GABA-B R1), their anchoring proteins (Gephyrin) and adhesion molecules (Neuroligin-2).ConclusionTaken together, such changes paint a picture showing a compromised integrity of the striatal GABAergic system under conditions of functional hyperdopaminergia, which may be of interest for several disorders of the central nervous system.
Keywords: dopamine homeostasis